Differences in Vitamin D Levels at Diagnosis and after Induction Phase Chemotherapy in Children with Acute Lymphoblastic Leukemia in Tertiary Hospital in West Java Indonesia - Mardhiya, Wan Rita; Suryawan, Nur; Setiabudiawan, Budi (Asian Pacific Journal of Cancer Care, 2023)
Objective: We examined differences of vitamin D levels at initial diagnosis and after induction phase chemotherapy in children with Acute Lymphoblastic Leukemia (ALL). Methods: A cross-sectional study was conducted on newly diagnosed children with ALL from October 2021 until October 2022 at Dr. Hasan Sadikin Hospital−Bandung, West Java, Indonesia. Vitamin D levels were measured twice using blood samples: at initial diagnosis and after the remission induction phase of chemotherapy. A paired t-test was applied and the value of p<0.05 is considered as statistically significant. Result: There were 53 subjects that fulfilled research criteria. Thirty−six subjects met the inclusion criteria while 17 were excluded. Majority of ALL patients were male (52.8%) and aged 1−10 years (83.3%). Mean vitamin D level of ALL children at initial diagnosis was 16.68±9,56 ng/mL. After the induction phase of chemotherapy, mean vitamin D level was 11.84±7,8 ng/mL. Paired t-test was performed to obtain p value = 0.000. Conclusion: The prevalence of hypovitaminosis D in ALL children is 88.8%. Vitamin D levels after chemotherapy are lower than at initial diagnosis.